2010
DOI: 10.2139/ssrn.1324016
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Value Creation: Evidence from Private Equity

Abstract: We examine deal-level data on private equity transactions in the UK initiated during the period 1996 to 2004 by mature private equity houses. We un-lever the deal-level equity return and adjust for (un-levered) return to quoted peers to extract a measure of "alpha" or abnormal performance of the deal. The alpha is significantly positive on average and robust during sector downturns. In the cross-section of deals, higher alpha is related to greater improvement in EBITDA to Sales ratio (margin) and greater growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 33 publications
(11 reference statements)
15
67
0
Order By: Relevance
“…Tax savings in the Leveraged Buyout (LBO) deals contribute to value creation (Acharya et al, 2009;Kaplan, 1989;Renneboog et al, 2007), as in our results. A financial conduit appears as another ownership mutation that optimally exploits the tax bankruptcy trade-o↵.…”
supporting
confidence: 80%
“…Tax savings in the Leveraged Buyout (LBO) deals contribute to value creation (Acharya et al, 2009;Kaplan, 1989;Renneboog et al, 2007), as in our results. A financial conduit appears as another ownership mutation that optimally exploits the tax bankruptcy trade-o↵.…”
supporting
confidence: 80%
“…In comparison, the same ratio is approximately 35% for comparable publicly listed companies. Acharya et al (2013) documented an average debt-to-enterprise value of 44% at exit, a level consistent with the results of Cao and Lerner (2009) for reverse leveraged buyouts (LBOs); they found that the leverage remained elevated after the public offering (47% for reverse LBOs versus 28% for non-buyout-backed IPOs).…”
Section: Sector Compositionsupporting
confidence: 64%
“…Axelson, Jenkinson, Strömberg, and Weisbach (2013) and Acharya, Gottschalg, Hahn, and Kehoe (2013) observed an average debt-toenterprise value of around 70% at the buyout transaction's inception. In comparison, the same ratio is approximately 35% for comparable publicly listed companies.…”
Section: Sector Compositionmentioning
confidence: 99%
“…Meuleman et al (2009) report that divisional buy-outs result in increased entrepreneurial activities compared to buyouts from other vendor sources. Acharya et al (2009) find for a sample of larger exited UK buyouts funded by more experienced PE firms, that included a small number of whole company PTPs but mainly divisional and secondary buyouts, that their alpha out-performance is related to greater improvement in EBITDA to Sales ratio during the private phase, relative to that of their quoted peers. Ernst and Young (2008) find for a sample of larger exited buyouts that average annual enterprise value grew significantly more than in public company equivalents, but that PTPs performed less well than divisional, secondary or private buyouts, while Ernst and Young (2009) for the UK find evidence of organic growth.…”
Section: Buy-outs In Generalmentioning
confidence: 88%